(3cJGH aVGFd GdbQBf GdYXje heYLRGJg hBOGHgs - (3CHh YHjO , GdbGSe Hf SdGe GdgQhj GdGROj GdNRGYj, CHh YHjO,J (B224 (3g` s ((3GdbOS GdTQja s)
(3ChdgG (B:s
(3jHOC HHGH aVd GdbQBf s
(3BNQgG (B:s
(3jfJgi HHGH GdeUMa jeSg GdeSde GdPi djS HWGgQ Gh GdeTQc s
(3HBNQg UhQ SeGYGJ YOjOgs
(3fbdI GdfGSN ef GUd SeGY TjNI GdPi bQCg Ydjg SfI (B704(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B101s
Keywords: (3Gdabg GdESdGejs